Training load determining sports performance in swimming - Guzman, M.; Brodáni, J. (Journal of Physical Education and Sport, 2023)
The representative from Slovak Republic, T.P., documented a noteworthy progression in sports performance within swimming disciplines during ATC 2020-2021. Notably, the 400 freestyle event showcased an impressive performance 3:49.03. In the analysis of the data, we used the method of studying the training diaries of the athlete from the annual training cycle 2022. From the point of view of general training indicators, we focused on days of loading (GTI 110), 111 training units (GTI 111), competitions / starts (GTI 112), load time (GTI 113), regeneration time (GTI 114) and days of medical incapacity (GTI 115). Of the special training indicators, we focused on total flown (STI 101), warm-up and swim-out (STI 102), aerobic endurance (STI 103), anaerobic endurance (STI 104), swim in race pace (STI 105), elemental arm swimming (STI 106), elemental leg swimming (STI 107), technical exercises (STI 108). A retrospective analysis delved into the classification of specialized and general training resources, pinpointing those with the highest correlation to sports performance in swimming. Employing non-parametric techniques, such as the Spearman correlation coefficient and decision trees of CHAID, facilitated the identifications of interactions and predictions. Among the special training indicators, factors influencing sports performance encompassed the volume of load swum at race pace (STI 105), the volume of warm-up and swim-out (STI 102), as well as the volume of aerobic and anaerobic endurance (STI 103 and STI 104). General training indicators also played a crucial role, with indicators such as the number of starts (GTI 112), occurrences of sick days (GTI 115), total load time (GTI 113), and number of training units (GTI 111) being key determinants of year-round athletic performance. The precise identification of training parameters in terms of volume and intensity the stage for rationalizing the periodization of the training process. This approach aims to align conceptual foundations enhance the tuning system for the observed swimmer's sports form, preparing them for upcoming top-tier world events.